Changes in plasma concentrations of S100A7 and S100A8 in dairy cows during pregnancy. (31st March 2018) - Elgawish, RA; Ogata, Y; Hidaka, T; Nii, T; Yoshimura, Y; Isobe, N
Contents: This study was carried out to examine the changes in plasma concentrations of the Ca‐binding antimicrobial proteins S100A7 and S100A8 during pregnancy in dairy cows. Holstein Friesian cows ( n = 19) were inseminated with Holstein Friesian semen. Blood was collected at days 30, 60, 90, 120, 150, 180, 210, 240 and 270 after insemination. Plasma was used for measuring the concentrations of S100A7 and S100A8. Both S100A7 and S100A8 concentrations showed similar patterns during gestation; they increased during the midgestation, between days 90 and 180, and then declined before calving. The findings indicated that plasma concentrations of S100A7 and S100A8 did not change significantly during pregnancy in cows. Further studies are required to determine the roles of S100A7 and S100A8 in physiological function during pregnancy in dairy cows.